Spray pyrolysis deposited zinc oxide films for photo-electrocatalytic degradation of methyl orange: influence of the pH - Quintana, M. (2003)
Zinc oxide films were made by spray pyrolysis equipped with an optical system for in-situ thickness measurement; zinc acetate water solution was used as spraying solution. The pH of the spraying solution was modified in order to increase the film porosity. Morphology and structure of the films were analyzed by scanning electron microscopy and x-ray diffraction, respectively. X-ray pattern revealed that films were zincite-like with a preferential growth in the [002]-direction. The optical absorbance of the methyl orange aqueous solution and the optical transmittance of ZnO-based films were measured in the wavelength range of 350-800 nm. Those measurements allowed both to control the photo-electrocatalytic degradation of methyl orange and to correlate the optical measurements with surface morphology of ZnO-based films. The zinc oxide based films obtained at different pH conditions of the spraying solution were brought into contact with methyl orange aqueous solution in a reactor in which the photo-electrocatalytically induced degradation under ultraviolet irradiation was investigated; the reactor was provided by an optical system to measure the in-situ optical transmittance of methyl orange solution. Results indicated that there is an increment of the active area of ZnO thin films when the pH of the spraying solution increases.